2008
DOI: 10.1007/s00264-008-0675-z
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomographic morphometry of thoracic pedicles: safety pedicle parameter measurement of the Chinese immature thoracic spine

Abstract: Our objective was to quantify the morphometric characteristics of the pedicles of the Chinese immature thoracic spine. A total of 120 patients aged 5-14 years underwent standard thoracic computed tomography (CT). The patients were grouped according to age: group 1 (5-8 years of age), group 2 (9-11 years of age) and group 3 (12-14 years of age). Images were reformatted, and multiplanar reconstructions were used to attain images of thoracic pedicles on sagittal, coronal and transverse planes. The measurements in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 12 publications
(9 reference statements)
2
8
0
Order By: Relevance
“…These divergent findings may be due to the smaller stature of Asian patients. 8 Regarding translaminar fixation, we conclude that it is possible to safely use 3.5 mm screws only in children older than 7 years old, finding similar to that of a previous study. 5 Our results clash, however, with those presented by Kretzer et al, 23 who found no size-related limitations for introducing translaminar screws.…”
Section: Discussionsupporting
confidence: 89%
“…These divergent findings may be due to the smaller stature of Asian patients. 8 Regarding translaminar fixation, we conclude that it is possible to safely use 3.5 mm screws only in children older than 7 years old, finding similar to that of a previous study. 5 Our results clash, however, with those presented by Kretzer et al, 23 who found no size-related limitations for introducing translaminar screws.…”
Section: Discussionsupporting
confidence: 89%
“…According to previous study, poor bone quality and small size of pedicles are the characteristics of young patients [ 14 ]. The bone of young children is very soft and easy to break, and the inner transverse diameters of the pedicles are smaller in very young children than in older ones [ 23 , 24 ], which may increase the difficulty of implantation. Pedicles may be anomaly or missing in some congenital scoliosis cases, which may contribute to construct/implant related complications.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the complicated inner structure and the particular location, the exact quantitative parameters of the thoracic pedicle, especially the outer pedicle width, cannot be definitely determined by the imaging methods currently in use, such as plain films and ordinary CT examination. Studies indicated that the pedicle parameters can be obtained accurately by using reformatted CT images (Li et al, 2004; Zheng et al, 2009; Chen et al, 2010). Therefore, the purpose of this study was to investigate the detailed three‐dimensional morphology of the pedicles from T1 to T12 using reformatted CT images.…”
Section: Introductionmentioning
confidence: 99%